Green Marketing Tools, Supply Chain, Religiosity, Environmental Attitude and Green Purchase Behavior - Aslamatis Solekah, Nihayatu; Handriana, Tanti; Usman, Indrianawati; Sani Supriyanto, Achmad (International Journal of Supply Chain Management, 2020)
The aim of the current study is to examine the role of green marketing tools, religiosity, supply chain management environmental attitude on green purchase behavior in the millennial generation based on these variables, then the Instruments are determined. Data collection methods in this study were questionnaires. The results of the collected 268 questionnaires of respondents were processed using descriptive and quantitative analysis tools using SEM (Structural Equation Model) analysis techniques with Stata 13. The greater green marketing tools which consist of Environmental Advertisement, Perception of eco-labels, Perception of an eco-brand, Trust in eco-label and eco brand the greater possibility to influence Green Behavioral Purchase (GBP). The greater Environmental Attitudes (EA) which consist of Environmental Knowledge (EK) and Environmental Value (EV) the greater positive effect on Green Behavioral Purchase (GBP). The greater religiosity value which consists of (religious belief), experiential ritualistic (religious feeling), Intellectual (religious knowledge), application consequences of religious effect the greater environmentally friendly attitude and Green Behavioral Purchase (GBP). Religiosity moderates the relationship between EA and GBP, so the relationship between EA and GBP is stronger for consumers with high Religiosity than consumers with lower Religiosity. This study will fill this gap. As a result, what this study proposes is the scarce and the new and original constructs respectively- The green purchasing behavior among millennials generation and also provides a framework for the study which makes it possible to explore the relation between green marketing tools, religiosity, environmental attitude and green purchase behavior.